Blueberry Bud Mite, Acalitus vaccinii (Keifer) (Arachnida: Acarina: Eriophyidae) - Harvey L. Cromroy; L. C. Kuitert (EDIS)
The blueberry bud mite, Acalitus vaccinii (Keifer), was originally described by H.H. Keifer in 1939 from specimens collected in North Carolina and, at that time, was called Eriophyes vaccinii Keifer. However, in 1965 when Keifer erected the genus Acalitus, the mite was transferred to this genus based on its morphological characteristics. This mite has been reported on both cultivated and wild plants of the genus Vaccinium. This document is EENY-186 (originally published as DPI Entomology Circular 130, updated for this publication), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2001.